2018
DOI: 10.1075/pc.18016.hoe
|View full text |Cite
|
Sign up to set email alerts
|

The linguistic marking of coherence relations

Abstract: Connectives and cue phrases are the most prototypical linguistic elements that signal coherence relations, but by limiting our attention to connectives, we are likely missing out on important other cues readers and listeners use when establishing coherence relations. However, defining the role of other types of linguistic elements in the signaling of coherence relations is not straightforward, and it is also not obvious why and how non-connective elements function as signals for coherence relations. In this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
0
10
0
1
Order By: Relevance
“…Das and Taboada (2018), for example, identified five categories of linguistic cues that can signal coherence relations: reference, semantic, lexical, syntactic, and graphical features. Hoek et al (2018) identified three distinct ways in which segment-internal elements, such as negation words and verb tense, can systematically interact with connectives to express a relation. Although these recent efforts have provided more insight into the types and functioning of segment-internal signals that can be identified in texts, more work is needed to investigate their effects on comprehenders.…”
Section: Coherence Relational Signalsmentioning
confidence: 99%
“…Das and Taboada (2018), for example, identified five categories of linguistic cues that can signal coherence relations: reference, semantic, lexical, syntactic, and graphical features. Hoek et al (2018) identified three distinct ways in which segment-internal elements, such as negation words and verb tense, can systematically interact with connectives to express a relation. Although these recent efforts have provided more insight into the types and functioning of segment-internal signals that can be identified in texts, more work is needed to investigate their effects on comprehenders.…”
Section: Coherence Relational Signalsmentioning
confidence: 99%
“…It is a longstanding idea that discourse relations are signaled through complex means that include, but go beyond, the presence of discourse markers (Asr and Demberg, 2015; Das and Taboada, 2018;Hoek et al, 2018;Prasad et al, 2010). Our study provides experimental evidence that confirms that readers are sensitive to subtle discourse cues, both in judging the coherence of discourse and in processing discourse relations.…”
Section: Discussionmentioning
confidence: 99%
“…In this precise study, Hoek et al (2018) do not distinguish among the coherence relations that may be and relations that may not be temporally characterized (e.g. in some cases, additive relations may have a temporal interpretation, which can be either synchronous or chronological).…”
Section: Implicit and Overtly Marked Temporal Relationsmentioning
confidence: 95%
“…They find a pattern in the distribution of explicit and implicit relations: relations such as Conjunction, Contrast, Concession, Synchrony, Asynchrony and Condition are most often overtly marked, whereas relations such as Cause, Instantiation and Restatement are most often left implicit. Furthermore, Hoek et al (2018) show, by means of a parallel corpus study, that the implicit versus overt marking status of coherence relations depends not only on the relation itself but also on the cognitive complexity associated to each type of coherence relations (based on the Cognitive Complexity of Coherence Relations framework developed by Sanders et al, 1992, and later work 1 ), among other factors. For example, they find that coherence relations with basic order are more often implicit than relations with non-basic order, and that conditional relations are less often implicit than causal or additive ones (Hoek et al, 2018: 127).…”
Section: Implicit and Overtly Marked Temporal Relationsmentioning
confidence: 96%
See 1 more Smart Citation